A Comparative Study Regarding the Performance of Corpuls 3 and Zoll Defibrillators - Mihaela MARIN; Florin Marian ILIE; Florin Bogdan MARIN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
The purpose of this paper is to provide a detailed and accessible overview of the Corpuls 3 and Zoll defibrillators, highlighting their features, functionalities and advantages in the monitoring and treatment of patients in emergency and intensive care settings. The comparison was based on seven main criteria: modularity, design, CPR capacity, performance, vital parameters monitoring, monitoring screens and maintenance costs.